As compet??ncias individuais em projetos da ind??stria 4.0 - Santos, Tain?? Alves dos (2018)
There is a growing demand for research related to "Industry 4.0" (I4.0) to provide insight into the issues, challenges, and solutions for project implementation and management in this scenario. There are studies that point to the high probability of the need for management of future competences, creating new requirements of skills, education and training aimed at the possibility of changing employees' profile (Antosz, 2018 In this context, it is sought to answer the following research question: "What are the individual competences required for employees in I4.0 projects?". The objective of this research was to identify the individual competences of professionals who work in the context of projects for the implementation and use of technologies related to I4.0. An exploratory literature review was also carried out to identify competences that had already been mapped by other researchers in the context of I4.0. As a research methodology, the Delphi method with three rounds was used to collect enough information to answer the proposed research question. From the publications identified in the literature review, the list of competences was generated that served as parameter for the first round of the Delphi method. In the second round, the revised list of competencies with the results from the previous phase was sent to the experts in order to identify which competencies were important to the project manager and to other team professionals. In the third round, the experts used a Likert scale to present the degree of importance of each competence to each audience. At the end of this stage, the final list was generated with the skills of the project manager and other project team professionals in the context of I4.0. To meet the research objective, a competency approach for I4.0 was proposed based on the findings made through the specialists' answers and a mental map developed from the literature. The results of this research contribute to the academy and provide insights for research into people development in project managed environments and educational guidance for the future workforce. For practitioners, this research contributes to the needs of building structures for the competence of I4.0.